A new species group to Edessa, the E. ovina group, with description of a new species (Heteroptera: Pentatomidae: Edessinae) from Brazil - Fernandes, Jose Antonio Marin; Da Silva, Valeria Juliete (Zootaxa, 2021)
The E. ovina group of species is proposed here to include Edessa ovina Dallas, 1851 from Trinidad and Tobago, Colombia, Paraguay, Brazil, Argentina (new records) and Guyana; E. impura Bergroth, 1891 from Brazil and Argentina (new record); E. sahlbergii Stål, 1872 restricted to Brazil; and E. graziae sp. nov. from Brazil and Argentina. The E. ovina group can be identified by the apex of the second pair of wings narrowing distally and by a tumid area on the ventral surface of the pygophore (male genitalia) projected posteriorly. Descriptions, measurements, and illustrations of the metasternal process, external and internal genitalia of male and female are provided. A map with the distribution of the species is presented. The holotype of Edessa ovina is designated here. Edessa argali Breddin, 1903 is considered a junior synonym of E. impura. Females of E. ovina and E. impura, and male of E. sahlbergii are described for the first time.